Rapid detection of Salmonella by low‐field NMR biosensor using long‐arm functional magnetic nanoprobes. (21st October 2022) - Dong, Qiuling; Liang, Xuehua; Xiong, Chunhong; Huang, Ganhui; Zhang, Jinsheng
Summary: Developing rapid detection tools and methods for foodborne pathogens has always been a research hotspot, which is undoubtedly very important for food safety. In this study, the preparation of functional magnetic nanoprobes and their application to detect target pathogens in a complex matrix by low‐field nuclear magnetic resonance (LF‐NMR) is demonstrated. The long‐arm functional magnetic nanoprobes were constructed by modification with polyethylene glycol (PEG) onto carboxyl‐modified magnetic nanoparticles (MNPs) and then reaction with biotin (Bio). Under the optimal conditions, the lower limit that can be detected in the PBS buffer system is 10 0 CFU/mL, and the detection of the actual sample matrix can be achieved 10 2 CFU/g. The practical application of LF‐NMR sensors to detect harmful pathogenic bacteria in food provides an efficient way of monitoring dangerous pathogenic diseases. Abstract : Schematic image of Bio‐PEG‐NMPs applied to DAS method coupled with LF‐NMR for Salmonella detection according to the value of T2. (A) The process of Bio‐PEG‐MNPs conjugation; (B) The principle of Salmonella detection based on NMR biosensor.